Analysis of the Relationship Between Intensive Care Unit Patient Characteristics and Patient Mortality at Adam Malik Hospital, Medan - Putera, Rahadhi; Hamdi, Tasrif; Zainumi, Cut Meliza (Perhimpunan Dokter Spesialis Anestesiologi dan Terapi Intensif, 2021)
Background: The intensive care unit (ICU) is a vital unit in hospitals that treats critical patients with physiological instability or organ failure.Objective: The general objective of this study is to determine the relationship between patient characteristics and ICU mortality, with the specific objective of analyzing the number of patients who died, characteristics (gender, age, type of disease, type of microorganism, route of admission, antibiotic use, tracheostomy time, and SOFA score)Methods: This study used a cross-sectional descriptive analytical design, Inclusion criteria were medical records of patients aged >18 years in the ICU ward.Result: Patient characteristics showed that most patients were admitted to the ICU via referral from other hospitals (132 patients). Fluoroquinolone antibiotics were the most frequently used (118 patients, 10.83%). 140 deceased patients had a sequential organ failure assessment (SOFA) score range of 10-11, with no significant difference (P 0.35). The highest mortality was observed in patients >65 years old (31.43%) and males (57.14%), often associated with respiratory diseases. Most deceased patients had a length of stay of 1-3 days (68.57%) and did not use ventilators (97.14%). Non-surgical patients had the highest mortality, with septic shock, acute myocardial infarct, and chronic heart failure as the primary diagnoses.Conclusion: Mortality of ICU patient in this research has a multifactorial cause consisting of admission route, microorganism type, tracheostomy timing and antibiotic usage.